Книга Справа Аляски Сандерс - Dicker, Joël, 1985- ([s.n.], 2024)
April 1999. Residents of Mount Pleasant, a peaceful town in New Hampshire, were shaken by a terrible murder - the mutilated body of a young woman, Alaska Sanders, was found on the shore of a local lake. The investigation was quickly completed, the police exposed the criminal and his accomplice. But eleven years later, the gruesome details of the case are resurfacing. Sergeant Perry Gehalowood, then handling the case, receives a disturbing anonymous letter. Did the police follow the wrong trail? Writer Marcus Goldman, well-known to readers for Joel Dicker's previous novels: "The Book of Baltimore" and "The Truth About the Harry Quebert Affair" joins the new investigation. Will Marcus be able to solve the incredibly complicated case again this time?